A SECURE AND ENERGY-EFFICIENT DATA TRANSMISSION FRAMEWORK FOR THE INTERNET OF THINGS - PRADEEPA, K.; Dr.M.Parveen (INFOCOMP Journal of Computer Science, 2023)
The idea of the Internet of Things (IoT) has recently received a lot of attention from both businesses and academics. In the IoT, a base station receives data from millions of sensor devices and processes it before using it to build various smart systems, such as the smart grid, smart city, and smart healthcare. To ensure the accuracy of the data gathered, a secure link must be established between base station and sensor devices. The findings of the data analysis will be erroneous and cause much more severe harm if the data that was collected is corrupt. Additionally, due to their extremely low-power computational processors, these IoT devices have a very low level of interactivity. These devices perceive their surroundings, produce data, and transmit the data to the base station through intermediary devices. Using some routing algorithms with the aim of low power consumption, the data is delivered to the base station. Energy efficiency should be taken into account as a crucial performance metric when utilizing low-power IoT devices to create a routing algorithm. Therefore, this paper proposed a secure and energy-efficient data transmission framework (SE-DTF) for IoT. This framework consists of three phases. The first phase is a public and secret key with a token sharing (IoT-PSKTS) algorithm which is used to prevent key leakages in the IoT. The second phase focuses on low power consumption using the Hierarchical Fuzzy Logic Clustering (HFLC) algorithm and Minimum Power Consumption Routing (MPCR) algorithm. The third phase focuses on safe data transfer employing two-tier cryptography with ciphertext shifting and token-based access control, together with HMAC-SHA1 signature. The experimental findings demonstrate how securely the IoT-PSKTS algorithm can share both a public and a secret key with a token. It also demonstrates that the MPCR with the HFLC algorithm outperforms other existing algorithms in terms of throughput, packet delivery ratio, and power utilization. Additionally, it demonstrates that the two-tier cryptography technique uses less energy and requires less computation time for encryption and decryption than other cryptography techniques now in use.